Re-irradiation strategies in combination with bevacizumab for recurrent malignant glioma - Schnell, Oliver; Thorsteinsdottir, Jun; Fleischmann, Daniel Felix; Lenski, Markus; Abenhardt, Wolfgang; Giese, Armin; Tonn, Jörg Christian; Belka, Claus; Kreth, Friedrich Wilhelm; Niyazi, Maximilian (Journal of Neuro-Oncology, 2016)
The place of bevacizumab (BEV) in salvage re-irradiation (Re-RT) settings of malignant glioma is poorly defined. In the current study risk/benefit profiles of two BEV-based Re-RT protocols were analyzed and compared with that of salvage BEV plus irinotecan (BEV/IRI). According to interdisciplinary tumor board recommendations, patients were assigned to one of three BEV-based treatment protocols: (1) BEV/IRI, (2) Re-RT (36 Gy/18 fx) with concomitant BEV (Re-RT/BEV), and (3) Re-RT with concomitant/maintenance BEV (Re-RT/BEV→BEV). Prognostic factors were obtained from proportional hazards models. Adverse events were classified according to the NCI CTCAE, v4.0. 105 consecutive patients were enrolled from 08/2008 to 05/2014. Patients undergoing Re-RT experienced longer time intervals from initial diagnosis to BEV treatment (median: 22.0 months vs. 13.7 months, p = 0.001); those assigned to Re-RT/BEV→BEV rated better on the performance scale (median KPSREC: 90 vs. 70, p = 0.013). Post-recurrence survival after BEV-based treatment (PRS) was longest after Re-RT/BEV→BEV (median: 13.1 months vs. 8 months, p = 0.006). PRS after Re-RT/BEV and BEV/IRI was similar. Multivariately, higher KPSREC and Re-RT/BEV→BEV were associated with longer PRS. Treatment toxicity did not differ among groups. Re-RT/BEV→BEV is safe, feasible and effective and deserves further prospective evaluation.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Bevacizumab; Glioblastoma; Radiotherapy; Re-irradiation; Recurrent glioma